Pós-modernismo: conceitos e experiências aplicados ao desenvolvimento de um blog interativo - Barbosa, Talita Bacetti (2013)
This monograph presents the creation and development of an interactive blog, in which were posted content related to postmodernism applied to graphic design, from an informal and more accessible language. In the monograph, it is initially analyzed and defined media blog tool, then an overview of the leading free platforms available are presented. It is shown concepts and key authors for compiling content. Then it is highlighted the creation of content posted on the blog as well as the development of its graphic interfaces. The experiment, which is validated through spontaneous forms and from a questionnaire with users, results in a visual experience, in general, convergent with the characteristics of each movement studied.